LAGU-LAGU TEMBANG SUNDA CIGAWIRAN - Oman Resmana (LP2M ISBI Bandung, 2016)
Tembang Sunda Cigiawiran is a kind of tembang presented by sekar (vocals) without gending accompaniment. The form of Ruumpaka used in this tembang is pupuh 17. I holds an important role as a medium of Islamic siar dissemination especially in Cigawir Village Sela Awi District Garut Regency. A Cigawiran singer must be sensitive towards laras that is delivered. Besides she must have a wide range of voice due to the coverage of varies tone area.